2021
DOI: 10.1038/s41467-021-26637-6
|View full text |Cite
|
Sign up to set email alerts
|

An innate contribution of human nicotinic receptor polymorphisms to COPD-like lesions

Abstract: Chronic Obstructive Pulmonary Disease is a generally smoking-linked major cause of morbidity and mortality. Genome-wide Association Studies identified a locus including a non-synonymous single nucleotide polymorphism in CHRNA5, rs16969968, encoding the nicotinic acetylcholine receptor α5 subunit, predisposing to both smoking and Chronic Obstructive Pulmonary Disease. Here we report that nasal polyps from rs16969968 non-smoking carriers exhibit airway epithelium remodeling and inflammation. These hallmarks of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 83 publications
2
12
0
1
Order By: Relevance
“…Accordingly, it was recently reported that expression of a COPD risk allele of CHRNA5 in epithelial cells leads to airway remodeling in vivo, increased proliferation and production of pro-inflammatory cytokines through decreased calcium entry and increased adenylylcyclase activity (Routhier et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, it was recently reported that expression of a COPD risk allele of CHRNA5 in epithelial cells leads to airway remodeling in vivo, increased proliferation and production of pro-inflammatory cytokines through decreased calcium entry and increased adenylylcyclase activity (Routhier et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…With a wide range of cell types able to produce or sense Ach, non-neuronal Ach serves as a versatile signaling molecule eliciting complex intercellular crosstalk with diverse outcomes; depending on the context, Ach may promote inflammation or conversely exert anti-inflammatory functions (Hollenhorst & Krasteva-Christ, 2021; Kummer & Krasteva-Christ, 2014; Sell et al, 2021). Accordingly, it was recently reported that expression of a COPD risk allele of CHRNA5 in epithelial cells leads to airway remodeling in vivo , increased proliferation and production of pro-inflammatory cytokines through decreased calcium entry and increased adenylyl-cyclase activity (Routhier et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, though we performed multiple conditional analyses (e.g., included smoking as a covariate and utilized DeepNull to model non-linearity), some detected loci, such as that near CHRNA 2, may be due to an association with smoking. Arguably, such loci remain relevant as smoking is an established cause of COPD, and, as demonstrated at the chromosome 15 locus, smoking-associated loci may have complex effects on phenotypes ([48, 49]). Lastly, our risk prediction model is agnostic to COPD-related phenotypes such as BMI, height, and smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Nous avions précédemment décrit l'expression des dif-férentes sous-unités des récepteurs nicotiniques dans le poumon humain [8]. Par des approches complémentaires in vitro, ex vivo, et in vivo chez la souris, nous venons de mettre en évidence le rôle du variant α5SNP dans le développement de lésions pulmonaires similaires à celles observées chez les patients présentant une BPCO [9]. Nous avons d'abord analysé le remodelage épithélial et l'inflammation sur des prélèvements humains de polyposes permettant notamment l'isolement de cellules épithéliales respiratoires.…”
Section: Récepteur Nicotinique De L'acétylcholine Et Bronchopneumopat...unclassified